Efficacy of a biobehavioral intervention for hot flashes: a randomized controlled pilot study. Issue 7 (July 2017) - Barton, Debra L.; Schroeder, Kelliann C. Fee; Banerjee, Tanima; Wolf, Sherry; Keith, Timothy Z.; Elkins, Gary
Abstract: Objective: The need for effective nonhormonal treatments for hot flash management without unwanted side effects continues. The primary aim of this pilot study was to evaluate the effect of combining a nonhormonal pharmacologic agent with a behavioral treatment for hot flash reduction. Methods: Seventy-one postmenopausal women were randomized to one of four groups: venlafaxine 75 mg + hypnosis (VH) versus venlafaxine 75 mg + sham hypnosis (VSH) versus a placebo pill + hypnosis (PH) versus placebo pill + sham hypnosis (PSH). Women recorded hot flash severity and frequency in a daily diary, in real time. The intrapatient difference in hot flash score (frequency × severity) at 8 weeks was analyzed using a General Estimating Equation model, using VSH as the referent arm, controlling for baseline hot flashes. Results: The active arms including PH or VH were not statistically significantly different than VSH ( P = 0.34, P = 0.05, respectively). Women in each active arm reported hot flash reductions of about 50%, with the PSH group reporting a 25% reduction. Women receiving the PSH reported statistically significantly smaller reductions in hot flash score than women in the referent VSH arm ( P = 0.001). There were no significant negative side effects during the course of the study. Conclusions: Hypnosis alone reduced hot flashes equal to venlafaxine alone, but the combination of hypnosis and venlafaxine did not reduce hot flashes more than either treatment alone. More research is needed to clarify whether combining hypnosis with a different antidepressant would provide synergistic benefits.